Innovation in Bromelain Enzyme Production from Pineapple and Honey and Its Characteristics - Weni Yulastri; Irdawati Irdawati; Yusrizal Yusrizal; Fathma Dwi Fatiha; Dwi Khayrun Nissha; Novicka Putri Anggraeni (Jurnal Penelitian Pendidikan IPA, 2024)
Bromelain enzyme is one type of protease enzyme that has the ability to hydrolyze protein peptide bonds into amino acids. Bromelain enzyme can be found in pineapple (Ananas comosus) which consists of 95% cysteine protease mixture. Bromelain is often used by athletes to treat physical injuries or minor wounds. In obtaining the bromelain enzyme found in pineapple, an isolation process is required, namely by extracting it extracellularly. The method in this study does not go through the cell breakdown process so that it is easier to separate from other impurities and does not mix with other cell materials. This study aims to develop an innovative method in the production of bromelain enzyme using pineapple and honey as raw materials and to evaluate the organoleptic properties, pH, and the presence of lactic acid bacteria. This study is a descriptive study presented in the form of graphs and images. From the research that has been done, it can be concluded that the manufacture of bromelain enzyme using pineapple and honey has succeeded in producing a product that has an organoleptic value of liking (60%), pH 3 (acid) with the number of lactic acid bacteria 2.43 cells/ml.